2019
DOI: 10.1115/1.4042461
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Failure Mechanism of Burn-Through During In-Service Welding on Gas Pipelines

Abstract: We conclude on the governing mechanism of burn-through and identify the area of highest risk for burn-through occurrence due to a specific combination of loading in this area. In order to investigate the mechanism of burn-through during in-service welding, an exploratory study combining both experiments and finite element simulations was presented. Combined with the theory of high-temperature failure, the initial position of burn-through and its mechanism were discussed. The results showed that burn-through wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…As the connection diameter became smaller, the restriction level increased. Qian et al [7] investigated the drilling mechanism during in-service welding through an exploratory study combining numerical experiments and simulations using the finite element method. The results showed that drilling was a type of fragile, intergranular rupture occurred in the cooling stage of in-service welding, starting in the partially melting zone and the cracks expanded along the weakened grain limits.…”
Section: Introductionmentioning
confidence: 99%
“…As the connection diameter became smaller, the restriction level increased. Qian et al [7] investigated the drilling mechanism during in-service welding through an exploratory study combining numerical experiments and simulations using the finite element method. The results showed that drilling was a type of fragile, intergranular rupture occurred in the cooling stage of in-service welding, starting in the partially melting zone and the cracks expanded along the weakened grain limits.…”
Section: Introductionmentioning
confidence: 99%